Non-relativistic conformal field theory in momentum space - Rajesh Kumar Gupta; Meenu (European Physical Journal C: Particles and Fields)
Abstract Non-relativistic conformal field theory describes many-body physics at unitarity. The correlation functions of the system are fixed by the requirement of the conformal invariance. In this article, we discuss the correlation functions of scalar operators in non-relativistic conformal field theories in momentum space. We discuss the solution of conformal Ward identities and express 2,3, and 4-point functions as a function of energy and momentum. We also express the 3- and 4-point functions as the one-loop and three-loop Feynman diagram computations in the momentum space. Lastly, we generalize the discussion to the momentum space correlation functions in the presence of a boundary.